Effect of Dapagliflozin on Outpatient Worsening of Patients With Heart Failure and Reduced Ejection Fraction: A Prespecified Analysis of DAPA-HF. Issue 17 (27th October 2020) - Docherty, Kieran F.; Jhund, Pardeep S.; Anand, Inder; Bengtsson, Olof; Böhm, Michael; de Boer, Rudolf A.; DeMets, David L.; Desai, Akshay S.; Drozdz, Jaroslaw; Howlett, Jonathan; Inzucchi, Silvio E.; Johanson, Per; et al.
Abstract : Background: In the DAPA-HF trial (Dapagliflozin and Prevention of Adverse Outcomes in Heart Failure), dapagliflozin, added to guideline-recommended therapies, reduced the risk of mortality and heart failure (HF) hospitalization. We examined the frequency and significance of episodes of outpatient HF worsening, requiring the augmentation of oral therapy, and the effects of dapagliflozin on these additional events. Methods: Patients in New York Heart Association functional class II to IV, with a left ventricular ejection fraction ⩽40% and elevation of NT-proBNP (N-terminal pro-B-type natriuretic peptide), were eligible. The primary outcome was the composite of an episode of worsening HF (HF hospitalization or an urgent HF visit requiring intravenous therapy) or cardiovascular death, whichever occurred first. An additional prespecified exploratory outcome was the primary outcome plus worsening HF symptoms/signs leading to the initiation of new, or the augmentation of existing, oral treatment. Results: Overall, 36% more patients experienced the expanded, in comparison with the primary, composite outcome. In the placebo group, 684 of 2371 (28.8%) patients and, in the dapagliflozin group, 527 of 2373 (22.2%) participants experienced the expanded outcome (hazard ratio, 0.73 [95% CI, 0.65–0.82]; P <0.0001). Each component of the composite was reduced significantly by dapagliflozin. Over the median follow-up of 18.2 months, the number of patients needed to treat with dapagliflozin to prevent 1 experiencing an episode of fatal or nonfatal worsening was 16. Among the 4744 randomly assigned patients, the first episode of worsening was outpatient augmentation of treatment in 407 participants (8.6%), an urgent HF visit with intravenous therapy in 20 (0.4%), HF hospitalization in 489 (10.3%), and cardiovascular death in 295 (6.2%). The adjusted risk of death from any cause (in comparison with no event) after an outpatient worsening was hazard ratio, 2.67 (95% CI, 2.03–3.52); after an urgent HF visit, the adjusted risk of death was hazard ratio, 3.00 (95% CI, 1.39–6.48); and after a HF hospitalization, the adjusted risk of death was hazard ratio, 6.21 (95% CI, 5.07–7.62). Conclusion: In DAPA-HF, outpatient episodes of HF worsening were common, were of prognostic importance, and were reduced by dapagliflozin. Registration: URL: https://www.clinicaltrials.gov ; Unique Identifier: NCT03036124. Abstract : Supplemental Digital Content is available in the text.